Picturing donations: Do images influence conservation fundraising? - Gabby Salazar (Public Library of Science (PLoS), 2021)
Many environmental organizations use photographic images to engage donors and supporters. While images play a role in fundraising, visual framing remains understudied in the environmental field. Few real-world experiments have examined which types of images result in higher donations to biodiversity conservation. We examined the role of images in conservation fundraising through a public experiment at Zoomarine, a marine park located in southern Portugal. Zoomarine runs a program called Dolphin Emotions where visitors pay to learn about dolphin biology and to interact with dolphins. We placed a donation box and a large informational poster about the Marine Megafauna Foundation, a conservation partner, in the lounge of the Dolphin Emotions program, which is open to participants and their families. The text on the poster, which solicited donations for the Marine Megafauna Foundation, was held constant, while four different image conditions were tested: dolphins, ocean wildlife, children, and people staring out from the poster (i.e., "watching eyes"). Each image condition was displayed for three days at a time and was on display for at least seven randomly assigned three-day periods over the course of 91 days. 20,944 visitors passed the donation box and the four poster conditions during this time and a total of € 952.40 was collected. The differences in mean donations in € per visitor per 3-day period were not statistically significant, F(3, 25) = 0.745, p = 0.54. Thus, we did not find that different images had a significant influence on donations to conservation. This may be due to our choice of visual frames or to the use of a donation box, which is a passive fundraising channel. Future research should examine how visual framing influences donations in other public settings and should test the influence of other visual frames on philanthropic behavior.